Intersectoral mental health promotion - A practice-oriented taxonomy of roles and a study of intersectoral dynamics - Carsten Hinrichsen; Line Nielsen; Nina Tamminen; Malene Kubstrup Nelausen; Amalie Oxholm Kusier; Ziggi Ivan Santini; Frederik Schou-Juul; Charlotte Meilstrup; Morten Hulvej Rod; Vibeke Koushede; Sigurd Lauridsen (Elsevier, 2022)
The need for strengthening intersectoral mental health promotion (MHP), together with prevention and treatment, is widely acknowledged. However, what roles are involved in intersectoral MHP and the interrelatedness of these roles have received limited attention in the existing literature. Therefore, the aim of this study is, first, to develop a practice-oriented taxonomy of roles within intersectoral MHP practices and, secondly, to investigate interactions across roles within the implementation of MHP practices. We conducted secondary analyses on data from a study (conducted between 2019 and 2021) evaluating MHP efforts within a Danish partnership. Data included 17 interviews, 10 telephone interviews, two group interviews, observational data, and documents. Analytical processes were inspired by the approach of Template Analysis and drew on results of prior evaluations of the partnership and literature on MHP. We propose a taxonomy consisting of five roles: 1) decision-maker; 2) MHP specialist; 3) MHP co-ordinator; 4) MHP practitioner; and 5) end user. Furthermore, applying these roles in a case study of the implementation of MHP practices in a Danish community setting, we elucidate and exemplify the interactions and interrelatedness across roles. The proposed taxonomy extends the current evidence-base for MHP by offering a language that can be used to clarify roles and functions within MHP practices across sectors and professions. It is, to our knowledge, the first of its kind specifically for MHP. Overall, our results add to the literature on MHP and facilitate a greater understanding of the intersectoral actions of MHP, which is relevant for strengthening practices and capacity building within MHP. Research on the transferability of the taxonomy and which competences are needed to successfully master the five identified roles is warranted.